2021
DOI: 10.1302/2058-5241.6.210062
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal balance: from theory to clinical practice

Abstract: Adequate sagittal balance (SB) is essential to maintain an upright, efficient, and painless posture. It has been shown that sagittal profile alterations affect quality of life of patients with a similar or even greater impact than chronic disease. Evaluation of the SB has gained much relevance in recent years, with recognition of its importance in the evaluation of spinal pathology. This review summarizes the basic principles of SB, aiming to obtain a practical, simple and understandable evaluation of the sagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The aim of the surgery is not only the correction of the kyphosis, but also correction of the all-sagittal balance parameters [13]. In order to improve the pain and the neurological symptoms, the cervical, thoracic and lumbar parameters should be corrected during the surgery [8,10]. The stable vertebra should be detected preoperatively in order to design a perfect construct for correction of the spine parameters [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the surgery is not only the correction of the kyphosis, but also correction of the all-sagittal balance parameters [13]. In order to improve the pain and the neurological symptoms, the cervical, thoracic and lumbar parameters should be corrected during the surgery [8,10]. The stable vertebra should be detected preoperatively in order to design a perfect construct for correction of the spine parameters [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical treatment of atypical Scheuermann's kyphosis is associated with multiple adverse effects, most importantly, junctional kyphosis [8]. It has been shown that spinal sagittal balance does not change significantly after surgical interventions, and is not correlated with preoperative thoracolumbar kyphosis [9,10]. In this article, we present a case of atypical Scheuermann's kyphosis who underwent surgical intervention with anterior release and posterior fusion with a 2-year follow-up and excellent outcome without any complications or adjacent segment disease.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the importance of a well-aligned spine has been increasingly recognized, regardless of the spine pathology [ 9 ]. Measurement of certain spinal coronal and sagittal radiological parameters has been recognized as crucial for the analysis of spinal deformities (including ASD) and planning of the treatment [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the tight relationship between sagittal plane deterioration and quality-of-life measures, Schwab et al [ 10 ] incorporated sagittal parameters into an adult spine deformity classification system and determined cutoff values for the most clinically relevant parameters in the sagittal profile (SVA, PI–LL, and PT) based upon multicenter data [ 11 ]. The global sagittal alignment of the spine, the degree of LL and the (mis)match between the latter and the PI may directly affect the health-related outcomes associated with quality of life, such as pain and disability [ 1 , 3 , 9 ]. HR instrumentation has been connected to subsequent sagittal malalignment of the spine, particularly due to the loss of LL, and further development of ASD, despite its positive impacts on the correction of the coronal-plane alignment [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation